Analisis Peramalan Permintaan untuk produk timbangan mekanik CV. Bina Karya Karawang - Samuel Mitra Purba; Kusnadi Kusnadi; Apid Hapid Maksum (Peneliti.net, 2021)
Bina Karya Karawang is an engineering company engaged in fabrication, machining, and stamping parts. Those who are suppliers of mechanical scales, one of which is a 300kg – 500kg mechanical sitting scale. Manual forecasting that has been done so far is often inaccurate so that the number of sales does not match, sometimes the sales target is minus and sometimes sales exceed the target. The lack of sales results causes a build-up of scales, while if the sales results exceed the target, it causes a lack of stock of existing goods and causes the obligation to ask for new stock of goods. Results of data processing and literature review that has been analyzed, the right method for forecasting production demand in CV. Bina Karya obtained data from January to June 2018, using the linear regression method. Because the data obtained is fluctuating or unstable. The results of the research that have been obtained, the amount of stock or production that must be made to meet consumer demand during January to December 2018 is January : 27 Units : February: 28 Units : March: 29 Units : April : 30 Units : May : 32 Units : June : 33 Units : July : 34 Units , August : 36 Units , September : 37 Units , October : 38 Units , November : 39 Units , December : 41 Units.